POLUDANUM’S INFLUENCE ON REPRODUCTIVE AND RESPIRATORY SYNDROME, TRANSMISSIBLE GASTROENTERITIS AND AFRICAN SWINE FEVER VIRUSES IN PRIMARY AND CONTINUOUS CELL CULTURES - D. V. Sharypova; I. Yu. Zhukov; Ali Mazlum; N. N. Vlasova; O. S. Puzankova; V. L. Gavrilova; A. S. Igolkin (Ветеринария сегодня)
Today studies of the influence of interferon synthesis inducer on human and animal body is a topical issue. Interferon synthesis inducers are substances of natural or artificial origin stimulating production of body’s own interferon. One of the synthetic inducers of interferon is Poludanum. It is used for stimulation of cell immunity which is capable of preventing infection and disease development and has antiviral and immunomodulatory effect. Poludanum mainly stimulates induction of α-interferon and, to a lesser extent, β- and γ-interferon in cells and tissues which prevent virus reproduction in a cell. The paper presents results of poludanum’s influence on reproduction of some porcine viruses in primary and continuous cell cultures by induction of interferon synthesis and other cytokines lowering the level of cell infection. As a result of performed tests it was found out that there is a link between introduction of interferon inducer and change in the PRRS, TGE, ASF virus reproduction. There was detected a high level of Poludanum’s interferon inducing activity in pig testicular primary cell cultures and spleen compared to the continuous pig embryo kidney (SPEV) and rhesus monkey kidney (MARC-145) cell lines. Poludanum’s interferon inducing activity was moderate for MARC-145 cells and it was not determined for SPEV.